Evaluation of the use of modern techniques and software in teaching mathematics in secondary schools - Al Migamsi, Fawzia Zuheir (Arab Journal for Sciences and Research Publishing, 2020)
The idea came from the low achievement of students in mathematics. A research work was conducted to find out the reasons for the low level of achievement of the second level of female students in mathematics at the 37th secondary school for girls and to develop suggested solutions and possible procedures. The aim of the study was to investigate the effect of the use of modern mathematical programs on the achievement of mathematics in the students of the second division at the 37th grade for girls. The study also found many results, including: the lack of use of diverse and sophisticated teaching methods and the lack of use of teachers to modern strategies and variety in teaching and helped modern programs students to understand the material and excel in it. The researcher recommended using the parameters of various and advanced teaching methods. To give the teachers courses especially with the developed curricula (modern) and be applied and not like the current courses that have been given to some of the parameters and did not benefit from them. The processing of laboratories and classrooms in all the requirements of the use of computer education, in order to facilitate the use of computer and computer software in the study of mathematics and the required software from languages ​​such as the language of Java and other programming languages.
Keywords: evaluation; use of technologies; modern software; teaching; mathematics; for secondary schools; teaching mathematics for secondary schools